Impact on environment assets: assessing post-flood environmental associated communicable diseases and the distributions through geospatial analysis - Ismail, Aziah (2017)
Flood causes serious health consequences especially on environmental-related diseases, particularty water and vector-borne diseases. Receding flood waters and pooling water in poodle provides perfect conditions for mosquito breeding, and increase in potential freshwater breeding sites results in larger numbers of mosquitoes, which would increase the potential for outbreaks of vector-borne diseases such as dengue fever. Contact with contaminated soil and water by animal urine will lead to leptospirosis. These diseases have relationship with the environment and other geographical factors and they could be transmitted not only to the vulnerable groups but also to those who are living near affected area. Therefore, the geospatial analysis is used to detenmine the relationship between: i. Cases of leptospirosis and leptospira isolated from the environment (i.e. water and soil) in Pasir Mas District, Kelantan. ii. Cases of dengue fever and distribution of Aedes mosquitoes in Kola Bharu and Bachok District, Kelantan.